2017
DOI: 10.1016/j.ypmed.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Primary HPV testing recommendations of US providers, 2015

Abstract: Objective To investigate the HPV testing recommendations of US physicians who perform cervical cancer screening. Methods Data from the 2015 DocStyles survey of U.S. health care providers were analyzed using multivariate logistic regression to identify provider characteristics associated with routine recommendation of primary HPV testing for average-risk, asymptomatic women ≥30 years old. The analysis was limited to primary care physicians and obstetrician-gynecologists who performed cervical cancer screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…While we did not examine provider characteristics in the current study, we hypothesize that they are important to understanding variation in cervical cancer screening and HPV DNA testing across counties and by NJCEED providers. Prior studies have shown that variation exists in providers’ adherence to screening guidelines and specifically in recommendations for HPV testing [ 16 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not examine provider characteristics in the current study, we hypothesize that they are important to understanding variation in cervical cancer screening and HPV DNA testing across counties and by NJCEED providers. Prior studies have shown that variation exists in providers’ adherence to screening guidelines and specifically in recommendations for HPV testing [ 16 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Against recommendations for age-specific practices, 31-43% of HCPs would prematurely initiate cervical screening before age 21 with either cytology or co-testing (16,17) . For women in the age range 21-29, practitioners generally over-screened by performing annual Pap tests (74% of OB/GYNs) (17) , 35-85% of HCPs (lowest proportion among OB/GYNs) inappropriately screened with the co-test (36,40,44,46) and recommended it yearly or every three years (13-42% of OB/GYNs, FPs, IMs, NPs, PAs) (16,44) . Cooper et al (2017) found that for women less than 25 years old, approximately 24% of OB/GYNs and 43-61% of FPs and IMs would incorrectly recommend the HPV test alone (46) .…”
Section: Practice and Intentionsmentioning
confidence: 99%
“…For women in the age range 21-29, practitioners generally over-screened by performing annual Pap tests (74% of OB/GYNs) (17) , 35-85% of HCPs (lowest proportion among OB/GYNs) inappropriately screened with the co-test (36,40,44,46) and recommended it yearly or every three years (13-42% of OB/GYNs, FPs, IMs, NPs, PAs) (16,44) . Cooper et al (2017) found that for women less than 25 years old, approximately 24% of OB/GYNs and 43-61% of FPs and IMs would incorrectly recommend the HPV test alone (46) . In women aged 30-65 years, reported co-testing use is highly variable: 28-80% among HCPs in the US (17,19,20,30,36,40) and 28% among OB/GYNs in Italy (39) .…”
Section: Practice and Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of primary care physicians and obstetrician-gynecologists found that approximately 30% of them would recommend asymptomatic women aged 30 years and older undergo annual screening with HPV testing. 52 Financial incentives/disincentives may be a solution, but the jury is still out as to whether payment-for-performance strategies improves adherence. 53 , 54 …”
Section: Sidementioning
confidence: 99%